"Evaluación de cuatro patrones de diferentes variedades de calabaza (¨Curcubita máxima) para el injerrto de aproximación de sandía (Citrullus innatus) (Thunb.) Matsum.& nakal, en la zona de Mocache, Provincia de los Ríos". - Salazar Cárdenas, David Isaac (2019)
The herbaceous graft is a very useful technique, based on rootstocks that provide properties of agronomic interest. It is a technique that respects the environment. Whose objective is the evaluation of different squash patterns (Cucurbita maxima), in the approach graft of watermelon (Citrullus lanatus), for its effect, the grafting was done 21 days after the emergence of the watermelon, when the rootstock as the pattern They obtained the first true leaves, and diameter of the stem are similar. The different vegetative variables were evaluated as: number of leaves, height of plant, diameter of stem, percentage of capture and percentage of mortality by treatment. A completely randomized design was applied with 4 treatments and 4 repetitions. An independent test was carried out, combining the N161 hybrid with different varieties of squash T1 (N161 x Moranga), T2 (N161 x Bárbara), T3 (N161 x Ver. Large), T4 (N161 x Rugged). The Tukey test was performed (P> 0.05), with a free Infostat statistical package. The results show that the use of the approach graft was successful, with the highest results the T1 (N161x Moranga), which presented a better height, number of leaves, stem diameter and percentage of capture. The best percentage of seizure was obtained in T1 with 90%. It was determined that the treatments T3 T4, obtained the lowest values for production cost ($ 0.35 / grafted plant) both, and the other treatments T1 and T2 ($ 0.36 / grafted plant), with higher values of production in the seedlings. It was concluded that the percentage of seizure is governed by certain aspects of compatibility which allows reactions in the seizure. Keywords: graft, rootstock, hypocotyl, approximation